Genomic analyses reveal moderate levels of ploidy, high heterozygosity and structural variations in a Colombian isolate of Leishmania (Leishmania) amazonensis (2020)
Leishmania amazonensis is one of the causative agents of the different forms of cutaneous leishmaniasis present in Latin America. This species has been isolated from humans and animals (canine/feline) in some endemic regions of Colombia. Therefore, L. amazonensis is of great relevance at the clinical and epidemiological levels in medicine and veterinary science. Until now, very few genomes from this species are available. Here, we report the complete genome sequence of a laboratory-adapted L. amazonensis strain isolated from a human patient with clinical manifestation of cutaneous leishmaniasis in Colombia. The genome sequence not only allowed inter and intra-species comparative analyses to be performed with the sequenced genomes of L. amazonensis strains from different geographical regions, but also increased our knowledge about the genomic behavior of this L. amazonensis Colombian strain. This isolate was also characterized in terms of single nucleotide polymorphisms, chromosome and gene copy number variations (CNVs). The results revealed moderate aneuploidy, CNVs in genes involved in the virulence, growth, and survival of the parasite, and in the distributions of the multicopy genes on some chromosomes, as well as a high level of heterozygosity. The data confirmed previous reports that identified unique variations in L. amazonensis, suggesting aneuploidy may not have a high fitness cost and may allow the rapid generation of diversity in Leishmania parasites growing normally. © 2019 Elsevier B.V.